VALIDITAS PERANGKAT PEMBELAJARAN DENGAN PENDEKATAN KONTEKSTUAL DALAM UPAYA MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP - Eva Yanti Siregar; Anni Holila; Marzuki Ahmad (Akademika, 2020)
The low ability to understand concepts is something that is still often found in mathematics learning, especially in secondary schools. One of the reasons is the lack of learning device that encourage students to be active in learning. Therefore, it is necessary to develop contextual learning tools in an effort to improve students' the ability understand mathematical concepts (AUMC) students. The type of research is descriptive quantitative. The research instrument was in the form of a learning device validation sheet. The research subjects were learning device which included lesson plans, student activity sheets (SAS), and students' AUMC tests. The object of research is the level of validity of the learning device. The results showed that the lesson plan with an index V of 0.72 was categorized as valid. SAS with an index V of 0.78 is categorized as valid, The AUMC-1 test and the AUMC-2 test with an index of V 0.76 and 0.74 were included in the valid category. It can be concluded that the contextual approach in improving student AUMC from the aspects of format, language and content is valid.